A Case of Diffuse Alveolar Hemorrhage Associated with High-Titer of MPO-ANCA Demonstrating Cytoplasmic Staining Pattern. (12th December 2019) - Ben Gabr, Jihad; Kato, Hiroshi
Abstract : Diffuse alveolar hemorrhage (DAH) is a life-threatening complication of ANCA-associated vasculitis (AAV) that requires urgent recognition and treatment. A presumptive diagnosis is often rendered without histopathology if concordant positivity of ANCA by indirect immunofluorescence (IIF) and ELISA assays, i.e., P-ANCA+/myeloperoxidase (MPO) Ab+ or C-ANCA+/proteinase-3 (PR3) Ab+, is documented in the context of pulmonary-renal syndrome or rapidly progressive glomerulonephritis. In this respect, the discordance between IIF and ELISA assays poses a diagnostic challenge in the absence of convincing histopathology and involves the risks of delaying the implementation of timely immunosuppressive therapy. Here, we report a 74-year-old woman who developed DAH and was found to have a high titer of MPO-ANCA exhibiting cytoplasmic staining on IIF, i.e., MPO-C-ANCA. The literature suggests that the availability of distinct epitopes on the MPO molecule dictates the perinuclear versus cytoplasmic staining pattern, which potentially explains the discordance between ELISA and IIF assays. Her DAH was controlled in association with seven sessions of plasmapheresis, methylprednisolone 1 gram daily for 3 days followed by 1 mg/kg/day, and rituximab. This case exemplifies the importance of consideration of pretest probability of suspected diagnosis that would realize a plausible interpretation of seemingly inconsistent serological profile and its effective incorporation into the diagnostic reasoning.